THE EFFECTIVENESS OF USING PICTURE WORDS INDUCTIVE MODEL (PWIM) IN WRITING A PROCEDURE TEXT - Prastama, Feriza Yudha; Rufinus, Albert; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The main interest of this research is to investigate the effect of the use of PWIM technique in improving the students ability in writing procedure text. In conducting this research, researcher used pre-experimental method which consisted of pre-test, treatment, and post-test. The technique in data collecting was measurement technique. The steps in data collecting were administrating pre-test, giving treatment, administrating post-test, and analyzing the test result. The result of this research showed the mean score of pre-test was 51.91 and the mean score of post-test was 63.97. it was also stated that the Effect Size (ES) of the treatment was 0.9 which means the use of PWIM was highly effective in increasing the students ability in writing procedure text. Key Words: Pre-Experimental, PWIM. Abstak: Penelitian ini bertujuan untuk menginvestigasi efek dari penggunaan teknik PWIM untuk meningkatkan kemampuan siswa dalam menulis teks prosedur. Dalam melaksanakan penelitian ini, peneliti menggunakan metodologi pre-experimental yang terdiri dari pre-test, treatment dan post-test. Teknik pengumpulan data yang digunakan adalah teknik measurement. Adapun langkah-langkah pengumpulan data adalah sebagai berikut; melaksanakan pre-test, memberikan treatment, melaksanakan post-test, dan menganalisa hasil tes. Hasil dari penelitian menunjukkan nilai rata-rata pre-test sebesar 51,91 dan nilai rata-rata post-test sebesar 63,97. Adapun Effect Size (ES) dari treatment sebesar 0,9 yang berarti penggunaan PWIM efektif dalam meningkatkan kemampuan siswa dalam menulis teks prosedur. Kata Kunci: Pre-Experimental, PWIM.